2002
DOI: 10.1002/j.1556-6978.2002.tb01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure and Construct Validity of the Counselor Skills Personal Development Rating Form

Abstract: The authors completed an exploratory factor analysis of the scores of 248 counselors‐in‐training on the Counselor Skills Personal Development Rating Form (CSPD‐RF; M. B. Wilbur, 1991). Participants' counseling program was accredited by the Council for Accreditation of Counseling and Related Educational Programs at a midsize western university. The authors of the CSPD‐RF hypothesized that the CSPD‐RF measured 2 factors: (a) personal development and (b) skills development. Factor analysis yielded 4 factors (Emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…They could request to complete the forms on the CD-Rom format or by printing the forms and mailing them in pre-addressed envelopes. Participants were asked to complete a demographic form that gained information about their supervision background, an informed consent agreement, and the Counselor Skill and Professional Development Rating Form (CSPD-RF) as modified by Torres-Rivera et al (2002;Wilbur, 1991). Responses were submitted online or through the mail.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They could request to complete the forms on the CD-Rom format or by printing the forms and mailing them in pre-addressed envelopes. Participants were asked to complete a demographic form that gained information about their supervision background, an informed consent agreement, and the Counselor Skill and Professional Development Rating Form (CSPD-RF) as modified by Torres-Rivera et al (2002;Wilbur, 1991). Responses were submitted online or through the mail.…”
Section: Methodsmentioning
confidence: 99%
“…The Counselor Skills Personal Development Rating Form (CSPD-RF) that was modified by Torres-Rivera et al (2002) was used to obtain feedback on the role-play skills interview. It was originally developed by Wilbur (1991) and then modified from a 7-point Likert-type scale to a 6-point scale, thus eliminating a middle response item.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of competencies within the framework of evaluation is considered to be crucial (Torres-Rivera et al, 2002). The National Career Development Association (NCDA, 1997) claims that the establishment of Counsellor Competencies serves as a guide for their training programmes and for an update of all those who wish to acquire or improve their skills.…”
Section: Models For Training Competencies Of Educational and Vocationmentioning
confidence: 99%
“…Indeed, Leverett-Main (2004) indicated that the skill of a counselor is less dependent on academic aptitude and more on personal qualities and interpersonal skills which might be best assessed through an interview process. Furthermore, TorresRivera, Wilbur, Maddux, Smaby, Phan, & Roberts-Wilbur (2002) argue that personal awareness was essential to the appropriate use of counseling skills.…”
Section: Figure 2 the Wellness Cube Model Bottom Viewmentioning
confidence: 99%